2015
DOI: 10.1080/10286020.2015.1048685
|View full text |Cite
|
Sign up to set email alerts
|

Norlignans fromPouzolzia zeylanicavar.microphyllaand their nitric oxide inhibitory activity

Abstract: Five new compounds, pouzolignan F [4-hydroxy-3-(3,5-dihydroxyphenyl)-2-[bis(4-hydroxy-3-methoxyphenyl)methyl]butyl acetate] (1), pouzolignan G [4-hydroxy-3-(3,5-dihydroxyphenyl)-2-[(4-hydroxy-3,5-dimethoxyphenyl)(4-hydroxy-3-methoxyphenyl)methyl]butyl acetate] (2), pouzolignan H [1,4-dihydroxy-3-(3,5-dihydroxyphenyl)-2-[bis(4-hydroxy-3-methoxyphenyl)methyl]butane] (3), pouzolignan I [1,4-dihydroxy-3-(3,5-dihydroxyphenyl)-2-[(4-hydroxy-3,5-dime thoxyphenyl)-(4-hydroxy-3-methoxyphenyl)methyl]butane] (4), and pou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…[3] Phytochemical studies on Pouzolzia genus revealed the presence of norlignans, prenylated isoflavones, triterpenes which have shown anti-inflammation and cytotoxic activities. [4,5] In our previous report, several norlignans were identified from aerial parts of P. sanguinea. Their chemical structures were remarkable not only by the loss of one carbon in lignan skeleton but also the presence of an additional benzene ring.…”
Section: Introductionmentioning
confidence: 92%
“…[3] Phytochemical studies on Pouzolzia genus revealed the presence of norlignans, prenylated isoflavones, triterpenes which have shown anti-inflammation and cytotoxic activities. [4,5] In our previous report, several norlignans were identified from aerial parts of P. sanguinea. Their chemical structures were remarkable not only by the loss of one carbon in lignan skeleton but also the presence of an additional benzene ring.…”
Section: Introductionmentioning
confidence: 92%
“…CD3OD,b) 125 MHz, c) 500 MHz; # δC of pouzolignan F, [4] @ δC of pouzolignan G. [4] The molecular formula of 2 was determined to be C27H30O9 by HR-ESI-MS analysis. b) 125 MHz, c) 500 MHz; # δC of pouzolignan H, [4] @ δC of pouzolignan L. [8] 3) and C-4 (δC 65.4) confirmed the appearance of one isoprene moiety. The above mentioned NMR data indicated 2 to be a norlignan, a specific class of compounds of Pouzolia species.…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…The above mentioned NMR data indicated 2 to be a norlignan, a specific class of compounds of Pouzolia species. [3, © 2020 Vietnam Academy of Science and Technology, Hanoi & Wiley-VCH Verlag GmbH www.vjc.wiley-vch.de 558 4,8] The HMBC correlations between H-1 (δH 3.75 and 4.06)/methyl group (δH 1.87) and carbonyl carbon (δC 172.7) indicated the position of the acetoxy group at C-1. The HMBC correlations between H-2′ (δH 7.04)/H-6′ (δH 6.96) and C-4′ (δC 146.0), H-5′ (δH 6.83)/methoxy protons (δH 3.92) and C-3′ (δC 149.2) suggested the location of the methoxy group at C-3′ and the hydroxy group at C-4′ of phenyl.…”
Section: Extraction and Isolationmentioning
confidence: 99%
See 2 more Smart Citations